Analisis faktor-faktor yang mempengaruhi risiko likuiditas pada bank yang terdaftar di BEI - Yumaita, Ria; Hady, Hamdy; Naluria, Febria (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study to determine the factors that can effect liquidity risk. The sample used in this study is banking companies listed on the Indonesian Stock Exchange in the 2015-2020 research period. The independent variable in this study were capital adequacy ratio, loan risk, profitability, bank size, liquidity gap, inflation rate and growth domestic product, while dependent variable in this study is liquidity risk. The number of research samples were 39 banking companies using purposive sampling technique. Based on the result of panel regression, it shows that capital adequacy ratio, loan risk, bank size, liquidity gap have a positive effect on liquidity risk, meanwhile profitability, inflation rate and growth domestic product have no effect on liquidity risk. The finding of this study expected to be a reference for banking companies in increasing the size of low-lying banks by increasing the assets owned by banks so that they can be channelled, paying more attention to and managing their capital well and maintaining high loan growth.